Operationalizing ʿaql as Moral Reasoning in Islamic Education: A Multi-Site Qualitative Study in Indonesia - Irgi Aqilul Fathoni; Yuan Remanita (Yayasan Centre for Studying and Milieu Development of Indonesia (CESMiD), 2026)
Moral reasoning is central to contemporary education, yet empirical studies rarely examine how the Islamic concept of ʿaql (reason) is operationalized within school practices. This comparative multi-site qualitative study investigates how moral reasoning is cultivated through Islamic education at two secondary schools in Tulungagung, Indonesia: SMK NU Tulungagung (vocational) and MA Al-Ma’arif Tulungagung (senior secondary). Data collection comprised non-participant classroom observations, semi-structured interviews with school leaders, teachers, and students, and analysis of curricular and institutional documents. Thematic analysis revealed an integrated pedagogical ecology in which dialogic classroom instruction, contextualized exemplars, reflective and problem-based tasks, structured extracurricular enactments of religious values, sustained teacher mediation, and formal competency articulation function as interlocking mechanisms for fostering moral reasoning. Both sites manifested these core mechanisms, though the pedagogical emphasis differed: the vocational site foregrounded applied problem-solving tied to everyday and occupational responsibilities, whereas the general secondary site emphasized doctrinal explication prior to application. By empirically operationalizing ʿaql as moral reasoning and demonstrating cross-contextual mechanisms, the study offers a transferable framework for faith-based curricula and teacher development that integrates ethical deliberation with cognitive and practical formation. Implications for policy and longitudinal research are discussed further internationally.